Efeitos da sobrecarga de frutose no perfil metabólico e no estresse oxidativo/nitrosativo no rim de ratas senescentes - Seraphim, Deborah Chianelli Costalonga [UNIFESP] (2017)
The aging process is a complex phenomenon that leads the body to several changes, affecting its integrity and resulting in chronic pathologies, which compromises health and quality of life of elderly people. Animals supplemented with fructose have been used as an experimental model for induction of insulin resistance. The objective of this study was to evaluate the metabolic effects and the levels of oxidative/nitrosative stress in the kidney of senescent rats with a high fructose intake. The animals were alocated into 4 groups, respectively, young control (J), elderly control (I), young fructose (JF) and elderly fructose (IF). Groups J and I received water and JF and IF received fructose (100g/L), both ad libitum. After 12 weeks of supplementation with high fructose, the animals were sacrificed to collect their kidneys, blood and the thoracic aorta. Blood was centrifuged and serum obtained for lipid profile, renal function, thiobarbituric acid reactive species (TBARS) and nitric oxide (NO). Renal tissue was homogenized and prepared for analysis of TBARS, NO, NO synthase enzymes (eNOS and iNOS), nitrotyrosine, superoxide dismutase-1, catalase and NF kB p65. Vascular reactivity was evaluated in the thoracic aorta of the animals. Results are presented as mean±SE, analyzed by statistical test one-way ANOVA with Newman-Keuls post-test or Student T-Test, when appropriate; significant at p <0.05. The fructose overload caused metabolic dysfunction and insulin resistance, confirming the efficacy of the chosen model. In this study we observed a body weight gain in the studied groups (except in the elderly fructose group), and an increase in general caloric intake, diuresis and adipose tissue; insulin resistance, increased fasting glucose, triglycerides and cholesterol were observed in the fructose groups. We also found a loss of renal function, increased oxidative/nitrosative stress and inflammation, with reduction of antioxidants and a lower vasodepressor response in the studied groups, especially those which consumed fructose. In summary, our data show that aging or high fructose intake contributed to the increase of oxidative/nitrosative stress in animals, demonstrating that at the dose and the period of fructose treatment utilized in this study, fructose was not able to aggravate several aspects which were already altered by aging. We believe that the high fructose intake simulates most of the effects of aging, and this understanding would be useful to prevent or minimize many of the alterations observed in the elderly.